Negotiations with Terrorist Organizations for the Release of Abductees: Between Declarations and Practice. The Israeli Case - Nagar, Nir Barkan (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
For decades, democratic countries have dealt with terrorist attacks carried out for the purpose of negotiations, which is the preferred modus operandi for some terrorist organizations. To what extent can a democratic regime effectively combat this abominable act while preserving a liberal or democratic character? Furthermore, these cases have become one of the most complicated dilemmas in both domestic and foreign policy. The prevalent opinion is that it is not possible to avoid meeting some of the demands of these terrorists. A government may even consent to paying a heavy price, so as to end the situation sooner. Media coverage influences this price, as extensive coverage of the terrorist attacks benefits the terrorists and thus increases their bargaining power. In contrast to the declarations of Israeli leaders in negotiations in cases of abduction, Israel has adopted a very flexible approach and is not interested in adopting the rigid approach of refusal to negotiate. The position of the opponents to negotiations with terrorist organizations is that the very negotiations with terrorist organizations legitimize them and the terrorist attacks, thus devaluing claims that terrorism is not a legitimate means of achieving one’s aims, and prevents the use of force in these situations. When all the prisoner exchange deals by the State of Israel are examined, approximately 7,500 terrorists have been released in the framework of the different deals, including terrorists with blood on their hands, in return for 14 living soldiers and civilians and 6 bodies of soldiers. A total of 1,027 terrorists were released in the Shalit deal alone.

W ciągu ostatnich dekad kraje demokratyczne padały ofiarą ataków terrorystycznych przeprowadzanych w celu nawiązania negocjacji, co jest preferowanym sposobem działania niektórych organizacji terrorystycznych. W jakim stopniu demokratyczne rządy mogą skutecznie zwalczać tę odrażającą praktykę, zachowując swój liberalny czy demokratyczny charakter? Przypadki te stały się także jednym z najbardziej skomplikowanych dylematów zarówno w polityce wewnętrznej, jak i zagranicznej. Przeważa opinia, że nie można uniknąć spełnienia niektórych żądań terrorystów. Rząd może nawet zgodzić się na zapłacenie wysokiej ceny, aby wcześniej zakończyć sytuację. Na wysokość tej ceny mają wpływ media, ponieważ szerokie relacje ataków terrorystycznych przynoszą korzyści terrorystom, a tym samym zwiększają ich siłę przetargową. W przeciwieństwie do deklaracji przywódców izraelskich odnośnie negocjacji w przypadkach uprowadzenia, Izrael przyjął bardzo elastyczne podejście i nie jest zainteresowany przyjęciem sztywnej postawy polegającej na odmowie negocjacji. Stanowisko oponentów negocjacji z organizacjami terrorystycznymi jest takie, że negocjacje takie legitymizują te organizacje i przeprowadzane przez nie ataki terrorystyczne, tym samym osłabiając twierdzenie, że terroryzm nie jest uzasadnionym środkiem do osiągnięcia własnych celów i uniemożliwia użycie siły. Po przeanalizowaniu wszystkich transakcji wymiany więźniów przez państwo Izrael, okazuje się, że około 7500 terrorystów, w tym terrorystów mających krew na rękach, zostało uwolnionych w ramach różnych transakcji w zamian za 14 żywych żołnierzy i cywilów oraz 6 ciał żołnierzy. W samej tylko transakcji Shalit uwolniono 1027 terrorystów.
Negocjacje z organizacjami terrorystycznymi w celu uwolnienia uprowadzonych: między deklaracjami a praktyką. Przypadek Izraela
Keywords: negotiations with terrorist organizations; fighting terrorism; national security; democracy; media; Gilad Shalit; negocjacje z organizacjami terrorystycznymi; walka z terroryzmem; bezpieczeństwo narodowe; demokracja; media; Gilad Shalit